Karakteristik Membran Selulosa Asetat dari Lidah Mertua Menggunakan Polietilen Glikol (PEG) Sebagai Pemlastis - Pramita, Ayu; Gudmanto, I'zaaz Ayundha (Universitas Bojonegoro, 2023)
Separation technology using membranes utilizes renewable materials using natural polymers such as cellulose. Cellulose in particular has great potential as an alternative material for membrane materials or its derivatives such as cellulose acetate. Mother-in-law's tongue (Sansevieria trifasciata) contains 50-60% cellulose. This research aims to be able to maximize cellulose fiber through the synthesis process. Cellulose acetate which is the main material for making membranes will be optimized into cellulose acetate membranes with variations in the addition of PEG composition. After the process is complete, the sample is filtered and then washed until the pH is neutral and dried at 45oC until cellulose acetate is produced in the form of dry powder. After that, tests were carried out using the Fourier Transform Infra-Red (FTIR) instrumentation to determine the functional groups formed in cellulose acetate from cellulose fibers of mother-in-law's tongue. Preparation of SA membrane using phase inversion technique with precipitation technique with solvent evaporation. Prepare a vial to add 4 grams of dissolved 10 mL of acetone, stir and add PEG 600 with variation 2; 4 and 6 mL until well mixed. Prepare a glass plate measuring 10×10 cm which has been taped on all sides and covered with clear plastic, after which the polymer solution is poured and leveled and then left to stand until the SA membrane is dry. The results of the SA membrane thickness test showed the highest value on the 6 mL SA/PEG membrane with a value of 2.225 mm. Analysis of the results of membrane morphology using Scanning Electron Microscope (SEM) instrumentation shows that on the surface of the 2 mL SA/PEG membrane with 1000x magnification no pores are visible, the 4 mL SA/PEG membrane begins to show pores, while the SA/PEG membrane 6 mL, it can be seen that the more number of pores that are formed